Study And Evaluation Of A Compartmental Silo (International Journal of Environmental Sciences, 2025)
To store different construction materials, industry need a bin-shaped storage facility so as to house various construction materials. Bins, bunkers, silos, and tanks are all terms used to describe buildings used to store bulk solids. Bins or bunkers are shallow structures used to store grains, cement coal, crushed stone, gravel, and other such identical materials. Silos are typically large constructions used to store resources like grain, wheat, cement, and other grains. The best place to store food grains, cement, or any other powdered material is in a silo. The silos are now used to store missiles because of technological advancements, in addition to holding the various materials described above. A compartmental silo (group of four silos) for storing any powdery material is taken into consideration in this work and subjected to various loading situations, including self weight, pressures of material, wind loads, seismic or earthquake loads, and variety of these loads combined. In the current research effort, the results against static loading, dynamic loading, and their combinations as well as the mode shapes and stress diagrams under different loading circumstances have been provided.